The role of age of first breeding in modeling raptor reintroductions - Morandini, V.; Dietz, Sabrina; Newton, Ian; Ferrer, Miguel (Ecology and Evolution, 2019)
The present biodiversity crisis has led to an increasing number of reintroduction programs, and this conservation method is likely to be increasingly used in the future, especially in the face of climate change. Many fundamental questions in population ecology are focused on the mechanisms through which populations escape extinction. 2. Population viability analysis (PVA) is the most common procedure for analyzing extinction risk. In the use of PVA to model the trajectories of reintroduced populations, demographic values are sometimes taken from other existing wild populations or even from individuals in captivity. 3. Density dependence in productivity is usually considered in viability models, but density‐dependent variation in age of first breeding is usually ignored. Nevertheless, age of first breeding has a buffering effect on population fluctuations and in consequence on population persistence. 4. We simulated the viability of Spanish Imperial Eagle (Aquila adalberti) and Osprey (Pandion haliaetus) populations using data from established and reintroduced populations in southern Spain. 5. Our results show that reduction in the age of first breeding is critical in the success of reintroductions of such long‐lived birds. Additionally, increases in productivity allow populations to growth at maximum rate. However, without considering variation in age of breeding, and the associated increasing overall productivity, reintroduced populations seem nonviable. 6. To ignore density dependence in age of breeding in PVA means that we are seriously limiting the potential of the model population to respond to fluctuations in density, thereby reducing its resilience and viability. Variation in age of first breeding is an important factor that must be considered and included in any simulation model involving long‐lived birds with deferred maturity. Peer reviewed